The role of neuroscience in enhancing chemistry concept understanding through brain-based learning approaches - Sofiyanita Sofiyanita; Santi Febri Arianti (Jurnal Konseling dan Pendidikan, 2025)
Understanding chemistry concepts remains a major challenge for students due to the abstract and complex nature of the subject. This literature-based qualitative study explores how neuroscience, particularly Brain-Based Learning (BBL) strategies, can enhance conceptual understanding in chemistry education. Neuroscience reveals how the brain processes, stores, and recalls information, offering a biological foundation for designing effective learning environments. The aim of this study is to analyze the impact of neuroscience-integrated approaches—especially brain-based teaching methods—on students' cognitive engagement, memory retention, and problem-solving abilities in chemistry. This study utilized a systematic literature review approach, analyzing 10 recent scholarly articles (2019–2025) from trusted academic databases. The data collection involved documentation of sources that discussed the role of neuroscience in education, brain-based learning, and chemistry pedagogy. The data were analyzed using conte   nt analysis, with themes such as emotional engagement, multisensory instruction, and prefrontal cortex activation. The results show that neuroscience-based strategies, particularly BBL, positively affect students’ motivation, retention of abstract chemistry concepts, and their ability to apply knowledge to problem-solving. Key findings highlight how emotional connection, active learning, and visual simulations help students form deeper and longer-lasting conceptual understanding. The study concludes that neuroscience offers both a theoretical and practical framework for transforming chemistry education into a more personalized, brain-friendly experience.